The diseases of airway-tracheal diverticulum: a review of the literature - Tanrivermis Sayit, Asli; Elmali, Muzaffer; Saglam, Dilek; Celenk, Cetin (Journal of Thoracic Disease, 2016)
Tracheal diverticulum (DV) is a type of paratracheal air cyst (PTAC) that is often asymptomatic and usually detected incidentally by imaging methods. Tracheal DV are divided into two subgroups: congenital and acquired. Dysphagia, odynophagia, neck pain, hoarseness, hemoptysis, choking, and recurrent episodes of hiccups and burping can also be seen in symptomatic patients. Thin-section multidetector computed tomography (MDCT) is useful for diagnosis of tracheal diverticulum. The relationship between DV and tracheal lumen can be demonstrated by axial, coronal, and sagittal reformat multiplanar images. Bronchoscopy can also be used in diagnosis for tracheal DV. However, the connection between DV and tracheal lumen can not be shown easily with bronchoscopy. Conservative treatment is the preferred treatment in asymptomatic patients. Surgical or conservative treatment can be performed for symptomatic patients, depending on patient age and physical condition.